Representation of punk rock from São Paulo of long playing album covers - Vargas, Herom (2020)
The aim of this article is to analyze the forms of representation of punk rock from São Paulo and ABC Paulista region in the images of long playing album covers. The notions of representation and culture, from Stuart Hall (2016) and cultural and semiosphere text, from Iuri Lotman (1996), will be the basis for understanding the cover as a cultural element of mediation. 26 records compose the analyzed corpus, with three seminal collections of the movement and 23 released by seven important São Paulo bands in the 1980s and early 1990s: Cólera, Garotos Podres, Inocentes, Mercenárias, Olho Seco, Ratos de Porão and Restos de Nada. The representations occur in figurative and abstract images in four primary ways: collage and “dirty” aesthetics; figuration of the punk character; images of violence, abjection and tension; criticisms of capitalism and the consumer society.